Preface of the "iterative Procedures for Solving Nonlinear Problems" - Cordero, Alicia; Magreñán, Á. Alberto; Torregrosa, Juan Ramón (AIP Conference Proceedings, 2020)
Ponencia de la conferencia "International Conference of Numerical Analysis and Applied Mathematics, ICNAAM 2017; The MET HotelThessaloniki; Greece; 25 September 2017 through 30 September 2017"
Keywords: Scopus(2)